Effect of Training Program Based on ADDIE Model on Pediatric Nurses' Performance Regarding Blood Transfusion: A Randomized Clinical Trial - Reyam Abdulredha Abbass; Monir Ramezani; Hossein Karimi Moonaghi; Adil Ali Hossein; Azadeh Saki; Hanieh Esfahani (Mashhad University of Medical Sciences, 2023)
Background: Clinical failures are considered as a serious problem in the health system and a threat for patients' safety. The nurses' performance was poor during the blood products transfusion for children. One of the main obstacles to implement a national blood policy in developing countries is the lack of trained staff.Aim: To determine the effect of a designed training program based on the ADDIE model (analysis, design, development, implementation, evaluation) on nurses' performance regarding  blood transfusion for children.Method: This randomized clinical trial (RCT) study was performed  in Bint Al-Huda teaching hospital at Al- Nasiriya City in Iraq. The study started from July 2021 to March 2021 and involved 60 nurses. Data was collected using a demographic data questionnaire and the observational checklist of  nurses' performance regarding transfusion of blood and blood products. At first, nurses' performance regarding transfusion of blood and blood products to a child was checked. Then, the intervention group received a designed training program based on the ADDIE model. Again, nurses' performance was assessed. Finally, data were analyzed with SPSS 25 software. P<0.05 was considered statistically significant.  Results: The scores of nurses' performance in pretest stage in the intervention and control groups was relatively similar (M=10.23±1.07 versus M=10.83±4.49; P>0.05), but in post-test stage, the scores of the intervention group were higher (M=36.40±3.08 versus M=10.85±4.53; P<0.001).Implications for Practice: According to the results, the designed training program based on ADDIE model can be used in pediatric setting to improve the nurses' knowledge and practices about blood transfusion.